Demographic profile of an indigenous community: The arians of Pakistan - Jamal Abdul Nasir; M. H. Tahir; Muhammad Riaz (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2013)
In this paper, a demographic study was conducted on Muslim Arians of Punjab, Pakistan. Hitherto no detailed demographic study has been conducted on Arians of Pakistan. The population composition of Arians residing in Punjab was evaluated. The survey was conducted in three Arians pre-dominated districts. Data was collected by interviewing ever-married women in the age group 15-49 years from a sample of 510 households. The analysis demonstrated that the sex ratios of Arians were higher than their national counterparts. Overall, among Arians though the literacy is high, the gender gap in education is visible and the level of education attained is low. Residence characteristics indicate urbanized nature of settlement. This study attracts the planners and administrators for micro-level planning towards the development of ethnographical surveys in Pakistan.
Keywords: 330; demographic variables; population structure; socio-economic profile; age-sex pyramid